Influence of patient related factors on health seeking behaviours among men with lower urinary tract symptoms attending surgical outpatient clinic at Meru Level Five Hospital, Kenya - Muriuki, Festus Mwendia; Kirigia, Consolata (International Journal Of Community Medicine And Public Health, 2020)
Background: Currently there are increased cases of men presenting with lower urinary tract symptoms (LUTS) especially in low resource countries. The purpose of this study was to establish the influence of patient related factors on health seeking behaviors for LUTS among men attending surgical outpatient clinic at Meru hospital, Kenya. Methods: Descriptive cross-sectional study design was used. Population involved 120 men suffering from LUTS, 2 physicians and 2 nurses. Questionnaires and interview guides were used for data collection. Study period was from August 2018 to March 2020. Results: Patients (67.0%) were aged between 61-70 years. Primary education level (68.8%). Farmers (72.0%) with income level of below Kenyan Shilling (Ksh.) 20,000. Logistic regression was used whereby p values (p≤0.05). The inferential statistics pointed out that patient related factors test items had a statistical significant influence since the p values were found to be less than 0.05 at 95% confidence interval. Conclusions: There was a significant negative influence of patient related factors such as lack of knowledge, low income levels and distance to health care facilities on health seeking practices. Patients sought medical attention when quality of their lives had been threatened. The study recommends adopting measures of rising awareness on need for seeking early medical attention and initiate outreach health services in underserved areas or through telehealth.